Determinants of Economic Growth in Java: Per Capita Expenditures, Population, and Contribution of Indonesian Democracy - Sari, Windy Fabrila (Journal of Development Economic and Social Studies, 2025)
The Golden Indonesia Vision 2045 targets sustainable, equitable and inclusive economic development, with an emphasis on the “Sustainable Economic Development” pillar. Java, as Indonesia's strategic region, is the highest contributor to the National Gross Domestic Product (GDP). In the 2019-2023 period, the global economic contraction due to the COVID-19 pandemic and the impact of simultaneous regional elections in Indonesia are challenges. This study examines the effect of per capita expenditure, population, and the Indonesian Democracy Index (IDI) on economic growth in Java. Using secondary data from six provinces and panel data regression analysis, the results show that per capita expenditure has a positive and significant effect on economic growth, while population has a negative and significant effect. IDI shows a positive but statistically insignificant relationship. The findings emphasize the importance of increasing purchasing power, population productivity through education and technology, and strengthening substantive democracy to achieve sustainable economic growth. This research provides insights for policy makers in optimizing regional potential to support Indonesia's national economic growth goals.